The Threat of the 21st Century: The New Nuclear Arms Race between the United States and Russia - Kunt, Melis Ege (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
Humanity first met with nuclear weapons in 1945 and faced its great destructiveness for the first time after bombing in Hiroshima and Nagasaki. Since then, nuclear weapons, which are among the central issues of international security, have become paranoia for both social scientists and societies, with the beginning of the Cold War and the increasingly greater powers to equip themselves with nuclear weapons. Nuclear weapons, which last more than 70 years in our lives, are still one of the biggest problems of the world, with the world being able to bring the end. Therefore, in 1968, Treaty on the Non-Proliferation of Nuclear Weapons was signed. Since then, the treaty has been the cornerstone of international efforts to prevent and ultimately eliminate the proliferation of these weapons to facilitate the enjoyment of nuclear energy for peaceful purposes. In addition, the United States and Russia, the two largest nuclear powers in the world, signed bilateral agreements that limited their nuclear ammunition. But there are attempts to terminate those in force. The termination of the agreements of the nuclear regime may indicate the beginning of a new nuclear arms race between the US and Russia. As a result of all these developments, the world is facing a new nuclear arms race and in the light of the current technological developments, it may have more dangerous consequences than the nuclear race experienced during the Cold War period.

ÖZ: ABD ve Rusya arasındaki mevcut nükleer rejimin sonlandırılması ofansif realist motivasyonlar sonucu nükleer belirsizliğe ve nihayetinde nükleer silahlanma yarışını artıracaktır. Ayrıca savunma teknolojilerindeki gelişme söz konusu olduğunda nükleer silahlanma yarışı geri dönülemez bir boyuta taşınabilir.
Master of Arts in International Relations. Institute of Graduate Studies and Research. Thesis (M.A.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Political Science and International Relations, 2019. Supervisor: Asst. Prof. Dr. Günay Aylin Gürzel Aka
Keywords: Nuclear weapons--Arms Race--United States--Russia; Nuclear arms control; Nuclear arm race; technological developments; arms control regimes